2022
DOI: 10.1155/2022/1731254
|View full text |Cite
|
Sign up to set email alerts
|

The Damage Constitutive Model of Sandstone under Water-Rock Coupling

Abstract: A constitutive model based on damage mechanics and statistical strength theory for sandstone under water-rock coupling is proposed and verified by laboratory tests and numerical tests. The damage mechanism of sandstone under the coupling action of water and force is clarified based on the microscopic test of sandstone under the coupling action of water and rock in this paper. The stress state of sandstone is determined by analyzing the results of laboratory tests. Based on the energy theory method, the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mechanical properties of coal and rock are easily affected by the occurrence environment (Liu, 2009;Yao et al, 2021). In recent years, with the progress and development of society, a large number of water conservancy and hydropower projects represented by the Three Gorges have been completed and put into use (Deng et al, 2017). The reservoir bank slopes of the Three Gorges and other reservoirs are immersed in water environment for a long time, which leads to the weakening of the mechanical properties of the slope rock mass and seriously affects the stability of the reservoir bank slopes.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of coal and rock are easily affected by the occurrence environment (Liu, 2009;Yao et al, 2021). In recent years, with the progress and development of society, a large number of water conservancy and hydropower projects represented by the Three Gorges have been completed and put into use (Deng et al, 2017). The reservoir bank slopes of the Three Gorges and other reservoirs are immersed in water environment for a long time, which leads to the weakening of the mechanical properties of the slope rock mass and seriously affects the stability of the reservoir bank slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Deep mining operations expose rock masses to a complex geological milieu characterized by elevated temperature, pressure, osmotic forces, and disturbances 1 6 . A thorough understanding of the mechanical response of the rock mass in this challenging environment is gained in the support of underground engineering initiatives 7 11 . Nevertheless, the energy conversion mechanisms governing sandstone under the combined effects of water and dynamic loading remain largely uncharted.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al (2021) conducted direct shear tests on phyllite under different immersion conditions and found that the cohesion was most affected by immersion conditions, the peak stress was second, and the internal friction angle was the smallest. Jiang et al (2022) established the damage constitutive model of sandstone under the water rock interaction through the experimental analysis, combined with the deduction of statistical strength theory and damage mechanics. Uniaxial compression characteristics, as one of the indispensable indexes to measure the basic physical and mechanical properties of rocks, are widely used in various engineering practices and scientific research work because of its relatively simple and clear test principles and easily realized test equipment.…”
Section: Introductionmentioning
confidence: 99%